Nursing Students' Perceptions on Healthcare-Associated Infection Control and Prevention Teaching and Learning Experience in Portugal - Parreira, Pedro (2022)
Healthcare-associated infections (HAI) are one of the major concerns worldwide, posing significant challenges to healthcare professionals' education and training. This study intended to measure nursing students' perceptions regarding their learning experiences on HAI prevention and control. In the first phase of the study, a cross-sectional and descriptive study with a convenience sample composed of undergraduate nursing students from Portugal, Spain, Poland, and Finland was conducted to develop the InovSafeCare questionnaire. In the second phase, we applied the InovSafeCare scale in a sample of nursing students from two Portuguese higher education institutions to explore which factors impact nursing students' adherence to HAI prevention and control measures in clinical settings. In phase one, the InovSafeCare questionnaire was applied to 1326 students internationally, with the instrument presenting adequate psychometric qualities with reliability results in 14 dimensions. During phase two, the findings supported that Portuguese nursing students' adherence to HAI prevention and control measures is influenced not only by the curricular offerings and resources available in academic settings, but also by the standards conveyed by nursing tutors during clinical placements. Our findings support the need for a dedicated curricular focus on HAI prevention and control learning, not only through specific classroom modules, innovative resources, and pedagogical approaches, but also through a complementary and coordinated liaison between teachers and tutors in academic and clinical settings.